Whole Genome Sequencing Provides New Insights Into the Genetic Diversity and Coat Color of Asiatic Wild Ass and Its Hybrids - Dong, Hong; Dong, Zheng; Wang, Fuwen; Wang, Gang; Luo, Xiaoyu; Lei, Chuzhao; Chen, Jingbo (Frontiers in Genetics, 2022)
The diversity of livestock coat color results from human positive selection and is an indispensable part of breed registration. As an important biodiversity resource, Asiatic wild ass has many special characteristics, including the most visualized feature, its yellowish-brown coat color, and excellent adaptation. To explore the genetic mechanisms of phenotypic characteristics in Asiatic wild ass and its hybrids, we resequenced the whole genome of Mongolian kulan (a subspecies of Asiatic wild ass) and 29 hybrids (kulan ♂×Xinjiang♀), and the ancestor composition indicated the true lineage of the hybrids. θπ-ratio, XP-EHH, CLR and θπ methods were used to detect the candidate regions of positive selection in Asiatic wild ass and its hybrids. Several immune genes (DEFA1, DEFA5, DEFA7, GIMAP4, GIMAP1, IGLC1, and IGLL5) were observed by the CLR and θπ methods. Also, KITLG located on chromosome 2 was detected by θπ-ratio and XP-EHH, and may be the crucial gene of coat color in Asiatic wild ass and its hybrids. Furthermore, the heatmap was able to show the clear difference in the haplotype of the KITLG gene between the hybrids and Asiatic wild ass group and the Guanzhong black donkey group, which is a powerful demonstration of the key role of KITLG in donkey color. Therefore, our study may provide new insights into the coat color and immunity of Asiatic wild ass and its hybrids.